Cytokinin Plant Hormones Have Neuroprotective Activity in In Vitro Models of Parkinson's Disease - Gonzalez, Gabriel; Grúz, Jiří; D'Acunto, Cosimo Walter; Kaňovský, Petr; Strnad, Miroslav (Molecules (Basel, Switzerland), 2021)
Cytokinins are adenine-based phytohormones that regulate key processes in plants, such as cell division and differentiation, root and shoot growth, apical dominance, branching, and seed germination. In preliminary studies, they have also shown protective activities against human neurodegenerative diseases. To extend knowledge of the protection (protective activity) they offer, we investigated activities of natural cytokinins against salsolinol (SAL)-induced toxicity (a Parkinson's disease model) and glutamate (Glu)-induced death of neuron-like dopaminergic SH-SY5Y cells. We found that kinetin-3-glucoside, cis-zeatin riboside, and N6-isopentenyladenosine were active in the SAL-induced PD model. In addition, trans-, cis-zeatin, and kinetin along with the iron chelator deferoxamine (DFO) and the necroptosis inhibitor necrostatin 1 (NEC-1) significantly reduced cell death rates in the Glu-induced model. Lactate dehydrogenase assays revealed that the cytokinins provided lower neuroprotective activity than DFO and NEC-1. Moreover, they reduced apoptotic caspase-3/7 activities less strongly than DFO. However, the cytokinins had very similar effects to DFO and NEC-1 on superoxide radical production. Overall, they showed protective activity in the SAL-induced model of parkinsonian neuronal cell death and Glu-induced model of oxidative damage mainly by reduction of oxidative stress.
Keywords: buněčná diferenciace; Cytokinins; Oxidative Stress; Isoquinolines; oxidační stres; Humans; oxidative stress; glutamate; cytokinin; neuroprotektivní látky; superoxidy; Plant Growth Regulators; neuron-like SH-SY5Y cells; Superoxides; Models, Biological; Glutamic Acid; buněčná smrt; Caspase 7; acetylcystein; lidé; neuroprotection; neurony; Neuroprotective Agents; kaspasa 3; Parkinson’s disease; Oxygen; kyslík; regulátory růstu rostlin; Caspase 3; kaspasa 7; phytohormone; Cell Differentiation; Neurons; biologické modely; nádorové buněčné linie; cytotoxicity; Cell Line, Tumor; salsolinol; Acetylcysteine; Cell Death; Parkinson Disease; isochinoliny; kyselina glutamová; cytokininy; Parkinsonova nemoc